Untangling the origin of the newcomer Phorcus sauciatus (Mollusca: Gastropoda) in a remote Atlantic archipelago - Baptista, Lara (2021)
The marine topshell Phorcus sauciatus is currently found along the temperate-subtropical shores of the Northeast Atlantic Ocean. Although present in the Iberian Peninsula, Madeira, and Canaries for centuries, P. sauciatus has only recently reached another oceanic volcanic archipelago in the region. In 2013, a small population was recorded for the first time in Santa Maria Island (Azores), widening its distribution around the entire island and to the neighbouring island of SAo Miguel in a short period of time. The success of such colonization of the remote archipelago by P. sauciatus still awaits an explanation. To better understand the populational dynamics of the species in the NE Atlantic Ocean, we used a molecular approach to evaluate the genetic structure of P. sauciatus aiming at the determination of a potential origin for the first individuals that reached the Azores. On the foundations of detailed oceanographic, palaeontological, and ecological data, we discuss the impact of climate change as a trigger for colonization of remote oceanic islands and suggest a mechanism that might explain the long-distance dispersal of the non-planktotrophic gastropod P. sauciatus across important biogeographical barriers in the NE Atlantic.